2023
DOI: 10.3390/coatings13081324
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Graphene Oxide Surfaces against Uropathogens

Samuel Belo,
Francisca Sousa-Cardoso,
Rita Teixeira-Santos
et al.

Abstract: Graphene and its functionalized derivatives have been increasingly applied in the biomedical field, particularly in the production of antimicrobial and anti-adhesive surfaces. This study aimed to evaluate the performance of graphene oxide (GO)/polydimethylsiloxane (PDMS) composites against Staphylococcus aureus and Pseudomonas aeruginosa biofilms. GO/PDMS composites containing different GO loadings (1, 3, and 5 wt.%) were synthesized and characterized regarding their morphology, roughness, and hydrophobicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The surface roughness was analyzed using a non-contact white light profilometer (Proscan 2000, Scantron Industrial Products Ltd., Taunton, UK) as described by Belo et al [ 36 ]. Quadruplicate measurements for each sample were performed (n = 4).…”
Section: Methodsmentioning
confidence: 99%
“…The surface roughness was analyzed using a non-contact white light profilometer (Proscan 2000, Scantron Industrial Products Ltd., Taunton, UK) as described by Belo et al [ 36 ]. Quadruplicate measurements for each sample were performed (n = 4).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have revealed that GN and its derivatives, such as GO and rGO, can inactivate both Gram-positive and Gram-negative bacteria in either planktonic or sessile states [37]. However, it has been evidenced that these graphene-based materials are more effective towards Gram-positive than Gram-negative bacteria [38,39]. While Gram-positive bacteria contain a plasmatic membrane and a thick peptidoglycan layer, Gram-negative bacteria have an outer membrane mainly composed of lipopolysaccharides, which may offer additional protection against chemical and physical stress [40].…”
Section: Introductionmentioning
confidence: 99%